2020
DOI: 10.1002/vms3.269
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Leucosporidium‐derived ice‐binding protein (LeIBP) on bull semen cryopreservation

Abstract: We examined the effect of ice‐binding protein derived from Leucosporidium (LeIBP) on the cryopreservation of bull semen and compared it with that derived from previously reported Antifreeze Protein III (AFPIII). Six concentrations of LeIBP (10 –1 ~ 10 4 μg/ml) and AFPIII (10 –1 ~ 10 4 μg/ml) were added to the bull semen extender, respectively. Sperm kinematic parameters were measured to examine sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Furthermore, ROS level was decreased in mouse oocytes vitrified with AFP III (Salvay et al, 2010 ). Another study also demonstrated that reduced glutathione/oxidative glutathione (GSH/GSSG) and total antioxidant capacity (TAC) were higher in bull semen cryopreservation with AFP III compared with the control group (Jang et al, 2020 ). In our study, the results also suggested that AFP III could protect the proteins associated with ROS production in mitochondria and GSH synthesis during sperm freezing and thawing.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ROS level was decreased in mouse oocytes vitrified with AFP III (Salvay et al, 2010 ). Another study also demonstrated that reduced glutathione/oxidative glutathione (GSH/GSSG) and total antioxidant capacity (TAC) were higher in bull semen cryopreservation with AFP III compared with the control group (Jang et al, 2020 ). In our study, the results also suggested that AFP III could protect the proteins associated with ROS production in mitochondria and GSH synthesis during sperm freezing and thawing.…”
Section: Discussionmentioning
confidence: 99%
“…AFP III improved survival by preserving protein expression and modulating the release of cytochrome C and free radicals at the molecular level. Jang et al [ 98 ] compared LeIBP with AFP III in the preservation of Korean bull semen and LeIBP showed better outcomes even in embryo formation after IVF.…”
Section: Applications Of Afps In Cryopreservationmentioning
confidence: 99%
“…In particular, embryos are very difficult to cryopreserve because of their size, survival sensitivity, and multi-compositional structure [ 7 , 8 ]. Several studies have reported that aberrant effects such as genotoxicity, necrosis, and abnormal apoptotic activity are responsible for the cytotoxicity observed in gametes and embryos during cryopreservation and vitrification [ 9 , 10 , 11 , 12 ]. To overcome these impediments, a number of researchers have studied the effect of co-treatment of gametes and embryos with protective adjuvants and freezing media, which was found to reduce toxicity as well as increase the success rate of artificial insemination.…”
Section: Introductionmentioning
confidence: 99%
“…Several organisms that live in extremely cold temperatures, including bacteria, fungi, microalgae, insects, crustaceans, and fish, produce specific proteins, called antifreeze proteins (AFPs) or ice-binding proteins (IBPs), that can inhibit ice recrystallization [ 9 , 11 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. In a subzero temperature environment, these proteins interact with ice crystals and regulate thermal hysteresis in order to stabilize the cell membrane [ 20 ].…”
Section: Introductionmentioning
confidence: 99%